Vanadium, rubidium and potassium in Octopus vulgaris (Mollusca: Cephalopoda) - Seixas, Sónia (2010)
The levels of vanadium, rubidium and potassium were determined in Octopus vulgaris caught during commercial fishing activities at three locations (Cascais, Santa Luzia and Viana do Castelo) in Portugal in autumn and spring. We determined the concentration of these elements in digestive gland, branchial heart, gills, mantle and arms in males and females. At least five males and five females were assessed for each season/location combination. Elemental concentrations were determined by Particle Induced X-ray Emission (PIXE). Vanadium was detectable only in digestive gland and branchial heart samples. Its concentration was not correlated with total weight, total length or mantle length. There were no differences in concentrations of V, Rb and K between sexes. There were significant differences in vanadium concentrations in branchial hearts in autumn between samples from Viana do Castelo and those from the other two sites. We found a significant positive relationship between the concentration of vanadium and those of potassium and rubidium in branchial hearts. Branchial hearts appear to play an important role in decontamination of V.